Future Biomarkers for Infection and Inflammation in Rheumatoid Arthritis - Cui S; Qian J (Dove Medical Press, 2023)
Shuang Cui, Jie Qian Department of Rheumatology, Affiliated Hospital of Nantong University, Nantong, Jiangsu, 226001, People's Republic of ChinaCorrespondence: Jie Qian, Department of Rheumatology, Affiliated Hospital of Nantong University, 20 Xisi Road, Nantong, Jiangsu, 226001, People's Republic of China, Email drqianjie@126.comAbstract: Rheumatoid arthritis (RA) increases the susceptibility to a variety of infections that are often difficult to diagnose and can be asymptomatic or symptoms are atypical. Usually, this is a great challenge for rheumatologists, because it is difficult to distinguish infection and aseptic inflammation at an early stage. Prompt diagnosis and treatment of bacterial infections in immunosuppressed individuals is critical for clinicians, and early exclusion of infection allows for specific treatment of inflammatory diseases and avoids the unnecessary use of antibiotics. However, for patients with clinically suspected infection, traditional laboratory markers are not specific for bacterial infection and cannot be used to distinguish outbreaks from infections. Therefore, new infection markers that can distinguish infection from underlying disease are urgently needed for clinical practice. Here, we review the novel biomarkers in RA patients with infection. These biomarkers include presepsin, serology and haematology, as well as neutrophils, T cells, and natural killer cells. Meanwhile, we discuss meaningful biomarkers that distinguish infection from inflammation and develop novel biomarkers for clinical applications, allowing clinicians to make better decisions when diagnosing and treating RA.Keywords: rheumatoid arthritis, infection, biomarker, inflammation, T cell